How do nurses use early warning scoring systems to detect and act on patient deterioration to ensure patient safety? A scoping review. (June 2019) - Wood, Colin; Chaboyer, Wendy; Carr, Peter
Abstract: Background: Despite widespread adoption of rapid response systems and the use of various early warning scoring systems, the detection of patient deterioration remains suboptimal, leading to the development of potentially avoidable serious adverse events. Why this occurs has been the focus of many investigations, but the complexities around advancing understanding that leads to effective actions are less evident. Objective: To better understand medical/surgical nurses use of early warning scoring systems. Design: A five-step process was used in this scoping review including: identify the research question; search and identify the relevant studies; selecting relevant studies; charting the data; and collate, summarize and report the results. The PRISMA extension for scoping reviews was used to guide this scoping review. Data Sources: In August 2018 a literature search was performed using the following medical subject headings: physiological, clinical deterioration, and the expanders early warning score, system, nurse attitudes, with Boolean operators in Ovid MEDLINE, CINAHL, and EMBASE databases. Review Methods: Extracted data included study aims, key findings, afferent/efferent focus and rapid response team description. Effective practice and organisation of care taxonomy guided data synthesis, before a thematic analysis was performed. Results: Of 120 unique articles, 23 were included in the scoping review (11 qualitative, 8 quantitative and 4 mixed methods studies). Fifteen studies focused on the afferent limb of the rapid response system whilst eight focused on both the afferent and efferent limbs. In the effective practice and organisation of care taxonomy twenty-two studies met criteria for quality and safety improvements while nineteen met criteria for referral, outreach and teams. Three themes, Inconsistent activation of the rapid response team; Barriers to following early warning scoring system algorithms; and Overreliance on scores emerged. Conclusion: Nurses aim to use early warning score systems to detect deterioration and ensure patient safety, however cultures, confidence and past experiences impact on rates of afferent limb failure globally. Simple to follow algorithms used in track and trigger charts are likely difficult for nurses to adhere to due to heavy workloads and challenges in getting medical officers to review within recommended time frames. Nurses rely heavily on the scores generated by early warning score systems but should aim to follow algorithms better and undertake holistic physical assessments to detect deterioration earlier and ensure patient safety is not compromised.